Investigating the Association between Orthopedic Fractures and Head Injury due to Road Traffic Accidents - Mubarak Ali Algahtany (Applied Bionics and Biomechanics)
Background. Traumatic head injury (THI) due to road traffic accidents (RTAs) is a global health problem. Studies exploring the association between RTA-related THI and concurrent orthopedic fractures are lacking. We aim to provide a detailed analysis of this association and its impact on inhospital outcomes. Methods. Retrospective analysis of RTA-related THI associated with orthopedic fractures admitted to a large tertiary center, Southwest, Saudi Arabia, over ten years. Descriptive statistics for participant demographics and clinical outcomes were represented by percentages. The associations between head injury diagnosis or orthopedic fractures region and patient demographics are analyzed using the Chi-square test. Post hoc analysis for the significant Chi-square values was carried out by calculating the significant adjusted residuals. Adjust p value was obtained by using the Benjamini-Hochberg procedure to control for multiplicity testing. A p value less than 0.05 was considered statistically significant. Results. Concurrent orthopedic fractures are present in one-tenth of RTA-related THI. The cohort was dominated by young males, with 46.5% of the population between 18 and 29 years old. There was a significant association between the head injury diagnosis and the region of orthopedic fracture (p=0.028). The type of head injury had significant associations with mortality and duration of hospital stay (p=0.039 and p=0.037, respectively). The region of orthopedic fracture significantly (p=0.018) affected the duration of hospital stay, with fractures in the clavicle/shoulder region significantly (p=0.035) having a short course of hospital admission. Conclusion. Orthopedic fractures concomitant with RTA-related THI are common. The associations between the two injuries tend to happen in specific patterns. The inhospital stay duration and mortality significantly correlated with the site of the head or orthopedic injury. Knowledge of these patterns improves the care of THI victims, triaging, and resource allocations.